The Relationship Between Multidimensional Poverty and Depression Among Single-Parent Families: A Comparative Analysis by Gender of the Household Head - Jinkyung Park; Donghyeon Kim; Daeyeon Jang (Healthcare, 2026)
Background/Objectives: This study examines gender differences in the relationship between multidimensional poverty and depression among single-parent families, drawing on the concepts of the feminization of poverty and dual vulnerability to inform gender-sensitive policy. Methods: Using a cross-sectional design, this study analyzed data from the 2024 Korean National Survey on Single-Parent Families, with a sample size of 3315 single-parent families. Multidimensional poverty was assessed across five domains: income, employment, housing, health, and social relations. Depression was measured using the Patient Health Questionnaire-9 (PHQ-9). Results: Poverty levels were highest in income, followed by housing, health, social relations, and employment. Female single parents experienced significantly higher poverty in income, employment, and social domains compared to males, while male single parents showed higher asset poverty. The proportion of respondents in the depressed group did not differ significantly by gender, though male and female single parents reached this similar overall level through partly different configurations of risk. Employment, health, and discrimination were common predictors of depression across genders, while lower education was an additional risk factor specific to female single parents. Depression scores rose in a linear, dose-dependent manner with the accumulation of multidimensional poverty for both genders, with a formal test indicating no significant overall difference in this pattern by gender. Conclusions: The findings suggest a critical need to shift policy from simple cash transfers to an integrated, multidimensional paradigm encompassing housing, employment, health, and stigma reduction. Policy interventions must prioritize gender-sensitive approaches tailored to the distinct risk configurations identified for male and female single parents.